Архаический эпос о зарождении армянской государственности - Вардумян, Гоар Д. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Արդի աշխարհաքաղաքական իրավիճակում առանձնահատուկ նշանակություն են ստանում հայոց պետականաշինության խնդիրները, որոնցում խորամուխ լինելու համար կարևոր է քննության առնել հին հայոց պետության ծագումը և նախնական ձևավորումը: Սույն գործընթացները յուրահատուկ արտացոլում են գտել Մովսես Խորենացու «Պատմութիւն Հայոց»-ում, որտեղ պահպանվել են վաղնջական էպոսի կարևոր դրվագներ: At the present stage of the geopolitical situation, the problems of the Armenian statehood and state-building are of particular importance, in connection with which it is necessary to examine the processes of its formation from the very beginning. These processes have found their reflection in “History of Armenia” by Movses Khorenatsi, which has preserved fragments of the archaic epic. They describe the valiant deeds of the first ancestor-patriarchs of the Armenians – Hayk, Aram and other Haykazuni-Haykids, whoAt the present stage of the geopolitical situation, the problems of the Armenian statehood and state-building are of particular importance, in connection with which it is necessary to examine the processes of its formation from the very beginning.
Keywords: Древняя и средневековая история